Interactive Influences Between Spot Blotch Pathogen and Saprophytic Fungi of Wheat at The Most Hot Spot Location of South Asia - S. L. Ranamukhaarachchi1, S. M. Shrestha2, Deepak Bhandari1* (Recent Research in Science and Technology, 2010)
Micro-organisms living on wheat phylloplane exert different kinds of interactions with each others. This study was conducted to find out the nature of interactions existing between spot blotch causal organism [Bipolaris sorokiniana (Sacc.) Shoem.] and well adapted saprophytic fungi of wheat (Triticum aestivum L.) leaves at the most hot spot location of spot blotch disease. Four most abundant saprophytic fungi were identified and evaluated for their interactions with B. sorokiniana. Pure cultures of selected fungi were procured from the spot blotch Infected wheat leaves following the single spore isolation method. Separate in-vitro dual culture studies in completely randomized design were carried out to assess the interactions between each pair of B. sorokiniana and selected rival fungus. The effects of interaction on radial growth of both fungi were measured and percent growth inhibition was calculated. Morphological study, viability test of the mycelium and sporulation ability of the fungi at the interface of dual culture were carried out. B. sorokiniana significantly inhibited the growth of Alternaria alternata and Nigrospora sp. in dual culture. In contrast, the interactions of B. sorokiniana with Epicoccum sp. and Curvularia sp. resulted in the suppression of mycelial growth of both fungi of each pair. The rates of growth inhibition during 1st and 2nd weeks of interaction were different in some tested fungi. The hyphael morphology of both fungi at the interface was normal in all pairs of fungi. The mycelia of all the fungi were viable at the interface of dual culture with B. sorokiniana. The sporulation ability of the tested fungi wasn’t affected by the interactions with B. sorokiniana except the Nigrospora sp. The well adapted saprophytic fungi of wheat leaves interact differently with spot blotch fungus B. sorokiniana.